Biogeographical scenarios modulate seagrass resistance to small‐scale perturbations. (31st December 2018) - Tuya, Fernando; Fernández‐Torquemada, Yolanda; Zarcero, Jesús; del Pilar‐Ruso, Yoana; Csenteri, Ina; Espino, Fernando; Manent, Pablo; Curbelo, Leticia; Antich, Adriá; de la Ossa, José A.; Royo, Laura; Castejón, Inés; et al.
Abstract: Seagrasses constitute a key coastal habitat world‐wide, but are exposed to multiple perturbations. Understanding elements affecting seagrass resistance to disturbances is critical for conservation. Distinct biogeographical scenarios are intrinsically linked with varying ecological and evolution backgrounds shaped across millennia. We addressed whether the resistance (change in shoot abundances) and performance (change in leaf morphology and growth) of the seagrass Cymodocea nodosa to a local stressor, light reduction, varied across three regions (Southeast Iberia, the Balearic Sea, and the Canaries) within the temperate northern Atlantic realm. We hypothesized that distinct biogeographical scenarios, in terms of distinct ecological/environmental conditions and genetic diversity of meadows, would affect seagrass resistance and performance, with flow‐on effects on associated epifauna. The same experiments, in terms of shading intensities, timing and duration, were replicated at three seagrass meadows within each region. Results demonstrated inter‐regional variation in the resistance and performance of C. nodosa . Under moderate and high shading, shoot abundance was abruptly decreased, relative to controls, in the Canaries with concurrent, but less accentuated, changes in leaf morphology and no changes in growth. In the other two regions, however, moderate and high shading had a negligible effect on shoot abundance, leaf morphology, and growth. Shading had no overall effect over the total abundance and assemblage structure of epifauna; these faunal attributes, however, varied between regions. Low seagrass resistance at the Canaries is linked with the peripheral distribution of the species there, favouring isolation and decreased genetic diversity. Synthesis . Different biogeographical scenarios shape seagrass resistance to local perturbations. From a conservation perspective, if resistance differs among biogeographical scenarios, universal conservation rules for seagrasses are challenging. Abstract : Different biogeographical scenarios shape seagrass resistance to local perturbations. From a conservation perspective, if resistance differs among biogeographical scenarios, universal conservation rules for seagrasses are challenging.